RECENT ADVANCES IN THE ROLE OF BACTERIAL ENDOPHYTES IN PLANT DISEASE MANAGEMENT - SANA BASHIR; EFATH SHAHNAZ; SABA BANDAY; ZAHOOR A. BHAT; MISBAH MUZAFFAR (The Bioscan, 2020)
Since times immemorial people have feared plant diseases due to the widespread destruction they caused directly or indirectly. Renaissance ushered in a new era of questioning everything resulting in the germ theory of disease and subsequently disease management with chemicals. However, with the surge in the environment consciousness and global climate change, research in plant pathology has seen a shift in research focus from chemical to biological management. Endophytes have played their role well but research has been limited, with only five per cent of the endophytes been effectively screened for their disease management properties. Endophytic bacteria live within the tissues of the plant but unlike plant pathogens do not cause harm to the plants invaded. Roots are considered to be the points of invasion for potential endophytes from soil to the roots and generally higher populations of endophytes are present in the below ground parts as compared to the above ground parts. Endophytes can colonise the same tissues as phytopathogens and hence act as biocontrol agents. A number of mechanisms are employed by the endophytes for disease management. Various researchers have reported the use of endophytes for the management of wilts, rots and damping off, blights and leaf spots, powdery mildews, rusts, downy mildews, basal rots and various post harvest fungal diseases. Diseases caused by nematodes and plant pathogenic bacteria can also be managed by the use of endophytes. The present paper reviews the recent research in the field of endophytes for the benefit of researchers and scholars.